Deposition of magnetite nanofilms by pulsed injection MOCVD in a magnetic field - Gounko, Iouri (My University, 2018)
This report is on the growth of Fe3O4 nanofilms on Al2O3(0001) and MgO(001) substrates with and without the presence of an external magnetic field using a pulsed injection metallorganic chemical vapour deposition (PI MOCVD) technique. The effects of growing magnetic oxide nanofilms in a 1 T field have been examined using various instrumental methods. It was found that the application of a magnetic field during PI MOCVD does not drastically alter the crystalline texture, surface morphology, and film thickness, but it significantly modifies the Fe3O4 film magnetisation and coercive field. Moreover, it was shown that the application of a 1 T field during the cooling of the sample also improves the magnetic properties. We believe that the large external field orients the magnetic spin structure at high temperatures (during growth or the initial stages of cool down) and that cooling through local magnetic ordering temperatures at Fe3O4 defect sites subsequently favours a ferromagnetic spin alignment. The control of magnetic properties of magnetite nanofilms by the application of magnetic fields during growth opens up new routes towards the fabrication and application of magnetic thin film devices.
Keywords: Magnetic nanofilms; Magnetite; MOCVD; Growth in magnetic field